Kontradiksi teori evolusi dan penciptaan manusia dalam perspektif Al-Qur’an dan sains - Sari, Meri Puspita (Maliki Interdisciplinary Journal, 2023)
The purpose of this study is to analyze the contradiction between the Qur’an and science regarding the phases of human creation. This research uses the method through library research (literature study). The type of data used is qualitative data. Sources of data used include primary and secondary sources. The primary data source is the Koran, while the secondary data source is journals and articles from an Islamic and scientific perspective. The results and discussion of this study indicate that the phases of human creation started from nutfah, ’alaqah, mudgah, bone formation, muscle formation, then perfected by the inhalation of the spirit, until it becomes the best form. Meanwhile, theoretically science, according to Charles Robert Darwin, humans are an evolutionary form of very simple organisms and argues that humans are descended from apes or chimpanzees and then evolved through natural selection. This research concludes that the validity of the theory of evolution is not accepted, because the Al-Quran has clearly written the phases of human creation which are in line with the findings of today’s modern scientists.